Website Information System Mayor Report as a Public Service in Palu City - Herlina Sakawati; Wiyarni Wiyarni; Muh Nur Yamin (Jurnal Aktor, 2024)
This study aims to determine the information system  of the Mayor Report website as a service in Palu City. This research uses a qualitative research approach with a descriptive qualitative type. Data collection techniques are carried out by observation, interview and documentation. The data analysis technique uses data condensation, data presentation, conclusion drawing and verification. The results of this study show that the information system   of the Mayor Report website in Palu City has been running well in accordance with the success model of the DeLone and McLean information systems. This can be seen from three indicators that have been running well, namely: system quality, usage, and net results received. Two indicators are doing quite well: service quality and user satisfaction. One other indicator is still not good, namely: the quality of information. The supporting factors for the information system of the Mayor Report website are the commitment of the Palu City Government, the environment and supporting infrastructure. While the inhibiting factor is network interference and there are still some complaints that do not contain complete information, and there are still empty complaints coming in.